2015
DOI: 10.1002/2014gl062773
|View full text |Cite
|
Sign up to set email alerts
|

China experiencing the recent warming hiatus

Abstract: Based on the homogenized data set, we analyze changes in mean temperature and some extreme temperature indices over China since 1961 and especially during the recent warming hiatus period (1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012) in a global average context. The result shows that the decrease of annual mean maximum has contributed most to the decreases in overall mean temperature and in diurnal temperature range (DTR) during the warming hiatus period. In most pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
119
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 44 publications
4
119
0
1
Order By: Relevance
“…Many studies indicate that the variations of extreme temperature are unbalanced and extreme temperature indices have an obvious trend turning in the 1990s [7,8]. Li et al [9] have analyzed the extreme temperature indices in China during nearly 50 years by using homogenized temperature data. The results show that the warming rate of mean annual maximum and minimum temperature decreased from 1998 to 2012, with a rate of over 0.4 • C decade −1 during the period 1961-1997, and the greatest decrease occurred in winter.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies indicate that the variations of extreme temperature are unbalanced and extreme temperature indices have an obvious trend turning in the 1990s [7,8]. Li et al [9] have analyzed the extreme temperature indices in China during nearly 50 years by using homogenized temperature data. The results show that the warming rate of mean annual maximum and minimum temperature decreased from 1998 to 2012, with a rate of over 0.4 • C decade −1 during the period 1961-1997, and the greatest decrease occurred in winter.…”
Section: Introductionmentioning
confidence: 99%
“…For example, although warming in the Northern Hemisphere is projected to increase in the future, the rate of global warming has slowed down over the past 15 years [23][24][25]. However, the response of vegetation to these trends remains uncertain, as the relationship between temperature and vegetation may change over time [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…For SCZ, because the LSTC is negative, the trend first increases at a rate of 0.09 °C/decade and then decreases at a rate of 0.21 °C/decade. Although there are debates regarding the global warming hiatus (Karl et al, ; Lewandowsky et al, ), the warming hiatus seems enhanced at region scales (Guan et al, ; Li et al, ). Moreover, Xie et al () found that the annual mean temperature in China exhibited a cooling trend during the recent global warming hiatus period, suggestive of a robust warming hiatus in China.…”
Section: Resultsmentioning
confidence: 99%